2013
DOI: 10.1097/sla.0000000000000269
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Congenital Intrahepatic Bile Duct Dilatation, Caroli's Disease and Syndrome

Abstract: LR for unilobar and LT for diffuse bilobar congenital IHBDD complicated with cholangitis and/or portal hypertension achieved excellent long-term patient outcomes and survival. Because of the bad prognosis of cholangiocarcinoma and the sizeable morbidity-mortality after LT, timely indication for surgical treatment is of major importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 37 publications
2
53
0
3
Order By: Relevance
“…The reported average prevalence is close to 7 %, but higher values of up to 25-30 % have been reported [ 10 ]. The prevalence of cholangiocarcinoma in a recent French multicenter study [ 10 ] was 5.2 %, but the same authors stated that this prevalence may be underestimated because the series is a retrospective and multicentric study and therefore patients with malignancy who did not require surgery were not included in the study.…”
Section: Evolutionmentioning
confidence: 80%
See 3 more Smart Citations
“…The reported average prevalence is close to 7 %, but higher values of up to 25-30 % have been reported [ 10 ]. The prevalence of cholangiocarcinoma in a recent French multicenter study [ 10 ] was 5.2 %, but the same authors stated that this prevalence may be underestimated because the series is a retrospective and multicentric study and therefore patients with malignancy who did not require surgery were not included in the study.…”
Section: Evolutionmentioning
confidence: 80%
“…Liver resection (LR) is considered as the treatment of choice for patients with localized forms without underlying chronic liver disease, when the impaired intrahepatic bile ducts can be completely resected [ 10 ]. In contrast, a diffuse bilobar disease is more challenging to cure and patients in whom radical resection cannot be performed are candidates for OLT [ 10 ] (Fig. 9.15 ).…”
Section: Type Vmentioning
confidence: 99%
See 2 more Smart Citations
“…This entity was fi rst described by Caroli et al [ 5 ] in 1958 and later classifi ed by Guntz et al [ 6 ] according to the morphology and the extent of intrahepatic bile duct dilatations. A recent multicenter study conducted by the French Association of Surgery [ 7 ] has shown that prevalence of intrahepatic lithiasis in patients with Caroli's disease is above 50 %, whereas in Eastern patients, it seems mainly related to biliary infestations and infections [ 8 ].…”
Section: Etiologymentioning
confidence: 99%